Brand Trust Saturation and Image-Driven Loyalty: Evidence from Consumer Satisfaction Pathways - Dirwan, Dirwan; Latief, Fitriani (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study aims to examine the effects of brand image and brand trust on customer loyalty, with customer satisfaction as a mediating mechanism among soft drink consumers. The study contributes by uncovering a saturation effect in brand trust, where trust functions as a baseline condition with limited incremental impact on loyalty, while brand image drives loyalty through both direct and satisfaction-mediated pathways. Using a quantitative design, data from 197 consumers were analyzed using PLS-SEM to test direct and indirect relationships. The findings show that brand image significantly influences customer satisfaction and loyalty, with satisfaction partially mediating this relationship. In contrast, brand trust positively affects satisfaction but does not significantly influence loyalty, either directly or indirectly. These results highlight asymmetric roles of brand constructs, suggesting that strengthening brand image remains critical for loyalty formation, while trust serves as a foundational but non-differentiating factor in mature markets.